Conductive Writing with High Precision by Laser‐Induced Point‐to‐Line Carbonization Strategy for Flexible Supercapacitors (Advanced Optical Materials 24/2021). Issue 24 (18th December 2021) - Guo, Heng; Yan, Jianfeng; Jiang, Lan; Qu, Liangti; Yin, Jiangang; Lu, Jiangang
Abstract : In article number 2100793, Lan Jiang and co‐workers propose a laser‐induced carbonization method with point‐to‐line carbonization strategy (LPLC method) and fabricate supercapacitors on polyimide (PI). The carbon linewidth decreases from over 150 μm to below 10 μm using this method. Carbon written by this method is suitable as electrodes for supercapacitors. The tree in the image shows that the LPLC method can write carbon lines with varying widths. Supercapacitors in the image show the application of the LPLC method.